2004
DOI: 10.1111/j.1464-5491.2004.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

A 14‐year prospective study of autonomic nerve function in Type 1 diabetic patients: association with nephropathy

Abstract: A 14-year prospective study of autonomic nerve function in Type 1 diabetic patients: association with nephropathy. Link to publication Citation for published version (APA): Forsén, A., Kangro, M., Sterner, G., Norrgren, K., Thorsson, O., Wollmer, P., & Sundkvist, G. (2004). A 14-year prospective study of autonomic nerve function in Type 1 diabetic patients: association with nephropathy. Diabetic Medicine, 21(8), 852-858. DOI: 10.1111/j.1464-5491.2004 General rights Copyright and moral rights for the publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
(36 reference statements)
1
31
0
1
Order By: Relevance
“…To match for age, all test results were expressed in age-related values-that is, SD-as previously described (17). An age-related value below -1.64 SD was considered abnormal and signified autonomic neuropathy (18).…”
Section: Evaluation Of Autonomic Nerve (An) Functionmentioning
confidence: 99%
“…To match for age, all test results were expressed in age-related values-that is, SD-as previously described (17). An age-related value below -1.64 SD was considered abnormal and signified autonomic neuropathy (18).…”
Section: Evaluation Of Autonomic Nerve (An) Functionmentioning
confidence: 99%
“…RR interval variation during deep breathing (expiration/inspiration [E/I] ratio) was used as a test of autonomic nerve function and an age-related E/I below -1.64 SD was considered abnormal [7].…”
Section: Examinationsmentioning
confidence: 99%
“…In a recent statement by the Toronto Diabetic Neuropathy Expert Group [4], it was suggested that the presence of one abnormal cardiovagal test identifies possible or early CAN, and that at least two abnormal HR tests are required for a definite or confirmed diagnosis of CAN. Nevertheless, several studies have pointed out that the RR E/I ratio is a simple, but especially informative, marker of CAN [6,38], and has the greatest specificity [4]. In addition, orthostatic hypotension (asymptomatic or symptomatic) along with HR test abnormalities (resulting in a decreased baroreflex gain in the present study) indicate more severe or advanced CAN [4].…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, a strong relationship was observed between the decreased baroreflex gain (but with no decreased RR E/I ratios) assessed during the squat test and the presence of microalbuminuria. In one prospective study, the progression of autonomic dysfunction in relation to nephropathy was followed for 14 years in T1DM patients [38]. Multiple regression analyses showed that the association between autonomic dysfunction and future albuminuria was due to the RR E/I ratio, supporting a role for this simple marker in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%